Serological Analysis and Drug Resistance of Chlamydia pneumoniae and Mycoplasma pneumoniae in 4500 Healthy Subjects in Shenzhen, China. (19th September 2017) - Du, Dong; Liao, Shuping; Wu, Yan; Jiao, Yang; Wu, Di; Wu, Weiqing; Yu, Dapeng
Abstract : Objective . To understand the prevalence and distribution of Chlamydia pneumoniae (CP) and Mycoplasma pneumoniae (MP) in the population and to provide a basis for the prevention and treatment of respiratory tract infection. Methods . This study included a total of 4500 healthy subjects who were given physical examination in Shenzhen People's Hospital from January to December in 2016. Venous blood was drawn from people to detect the MP- and CP-specific IgG and IgM in the serum using chemiluminescence immunoassay (CLIA). The relationship of MP and CP infections with patient age, seasons, and percentage of infections was analyzed. Conclusion . CP and MP cause high rate of asymptomatic infection, which may be associated with the high incidence of CP and MP infection, especially in children and the elderly population. Therefore, the implementation of effective and practical prevention measures has become an urgent need. MP culture and drug sensitivity test should be performed as early as possible in patients with manifested MP infections in order to ensure timely and proper treatment and to reduce the emergence of drug-resistant strains.